The Differences Between Certified And Non-Certified English Teachers In The Teaching And Learning Process - Roslina Roslina; Tekky Geriasti Pega’ Bella; Fernandes Arung (STAI Miftahul Ula Nganjuk, 2017)
This research was conducted to analyze the differences between certified and non-certified English teachers in the teaching and learning process. The researcher formulated the objective of the research was to find out the differences between certified and non-certified English teachers in the teaching and learning process. Based on the objective of the research above, so the researcher came to analize the differences between certified and non-certified English teachers, they were one of certified English teacher in SMP Neg. 1 Kolaka and one of non-certified English teacher in SMK Negeri 1 Kolaka. The design of the research, the researcher used a descriptive qualitative analysis. In conducting the research, the researcher used two kinds of data collection, they were interview and observation. In analysis of the data, the researcher used techniques of data analysis by Miles and Huberman, namely data reduction, data display and verifying and conclusion. In representing the analysis, the researcher mentioned the findings of certified and non-certified English teachers in the teaching and learning process. Furthermore, through out, the analysis, the researcher explained that certified and non-certified English teachers had some differences in the teaching and learning process. They showed differences in some indicators, they were material mastery, systematic presentation, methods application, using media, performance and motivation. Based on the finding and analysis, the researcher made conclusion that certified English teacher didn’t have all indicators in his teaching and learning process. Conversely, non-certified English teacher had all indicators in his teaching and learning process. In other words, non-certified English teacher had good quality than certified English teacher.